Two women in wheelchairs - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women in wheelchairs. One woman holds a sign that reads, "We love our gay children". The second woman holds a sign that reads, "Gay rights are human rights" during the National March on Washington for Lesbian and Gay Rights.